Pengembangan Modul Pencemaran Lingkungan Berbasis Problem Posing Disertai Spider Concept Map untuk Memberdayakan Keterampilan Proses Sains dan Kemampuan Menganalisis Siswa SMAN 1 Sumberlawang - WAHYONO, WAHYONO; SUDARISMAN, SUCIATI; SUTARNO, SUTARNO (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
The research and the development of the modules aims to know: 1) The characteristic of environmental pollution module based on problem posing with spider concept map; 2) The procedure of developing environmental pollution module based on problem posing with spider concept map; 3) The feasibility of environmental pollution module based on problem posing with spider concept map to empower students’ science process skills and students’ analyze abilities; and 4) Effectiveness of environmental pollution module based on problem posing with spider concept map to to empower students’ science process skills and students’ analyze abilities. The method used in the research is Research and Development (R&D) modification of Borg & Gall (Tim Puslitjaknov, 2008: 10-11). The subject used in preliminary field test consisting of 10 students’, the main field subject consisting of 10 students’ and opeational field subject consisting of 32 students’ SMAN 1 Sumberlawang. The instruments used in the research, mainly: questionaire, observation, interview and test. The operational field was conducted using one group pretest-postest design. Students’ science process skills and students’ analyze abilities were tested by paired sample t-test and counted by normalized gain score. The results of the research can be concluded that: 1) The characteristic of vironmental pollution module based on problem posing with spider concept map, mainly: aspect of students’ science process skills and students’ analyze abilities, science literate abilities (be able to understand, read, write and think in terms of science); 2) The development of environmental pollution module based on problem posing with spider concept map used modification Borg & Gall, mainly: preliminary research, planning, developing the initial products, preliminary field test, major product revision, main field test, the operational product revision, operational field, revision of the final product, the dissemination and the implementation of the product; 3) The feasibility of environmental pollution module based on problem posing with spider concept map average obtained is 3,51 that’s “very good” categories; and 4) The environmental pollution module based on problem posing with spider concept map is effective to empowering students’ science process skills with 0,60 N-gain score that’s “middle” categories and empowering students’ analyze abilities with 0,57 N-gain score that’s “middle” categories.